The Educational Management based on Student Behavior at SMPIT Insan Kamil, South Halmahera - Asep Sofyan; Abdul Wahid; Juhrah M. Arib (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
This study aims to analyze the implementation of the educational management based on student behavior at SMPIT Insan Kamil, South Halmahera. This research is a field research and uses a qualitative method with a descriptive approach. Data collection techniques are observation, interviews, and documentation. Primary data were obtained from field observations, and interviews with research informants consisting of students and teachers, while literature such as journal articles and books were used as secondary data. The research data were analyzed using inductive analysis. This study found that the implementation of student behavior-based education management at SMPIT Insan Kamil was carried out through two activities, namely intracurricular and extracurricular activities. Character values obtained from intracurricular activities include Islamic religious values, discipline, honesty, and responsibility. While the character values obtained from extracurricular activities include Islamic religious values, discipline, honesty, responsibility, high curiosity, tolerance, national spirit and love for the homeland, respect for achievements, and care for the environment and social.